Unusual etiology for upper gastrointestinal bleeding in a previously healthy child - Madhuradhar Chegondi; Tara Loux; Balagangadhar R. Totapally; Cathy A. Burnweit (Elsevier, 2015)
Paraduodenal hernia (PDH) is the most common congenital internal hernia and rarely presents in pediatric age group with acute abdominal symptoms. We report a six year old boy who has recurrent vague abdominal pain, vomiting for six months and massive upper GI bleed at admission, found to have left sided PDH and small bowel ischemia intraoperatively and underwent small bowel resection and PDH repair. He was discharged from hospital on day 6 postoperative day after uneventful course.